2003
DOI: 10.1118/1.1633105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the first commercial Monte Carlo dose calculation engine for electron beam treatment planning

Abstract: The purpose of this study is to perform a clinical evaluation of the first commercial (MDS Nordion, now Nucletron) treatment planning system for electron beams incorporating Monte Carlo dose calculation module. This software implements Kawrakow's VMC++ voxel-based Monte Carlo calculation algorithm. The accuracy of the dose distribution calculations is evaluated by direct comparisons with extensive sets of measured data in homogeneous and heterogeneous phantoms at different source-to-surface distances (SSDs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 19 publications
6
75
0
8
Order By: Relevance
“…Many MC packages such as EGSnrc, (1) PENELOPE, (2) MCNP, (3) and GEANT4 (4) have been used and benchmarked with experimental data very accurately in a variety of clinical radiotherapy scenarios. There are a variety of MC‐based dose calculation algorithms used in radiotherapy treatment planning systems (TPS) 5 , 6 , 7 , 8 . Generally, these algorithms make some sacrifices to gain computational efficiency required to achieve appropriate statistical uncertainty levels.…”
Section: Introductionmentioning
confidence: 99%
“…Many MC packages such as EGSnrc, (1) PENELOPE, (2) MCNP, (3) and GEANT4 (4) have been used and benchmarked with experimental data very accurately in a variety of clinical radiotherapy scenarios. There are a variety of MC‐based dose calculation algorithms used in radiotherapy treatment planning systems (TPS) 5 , 6 , 7 , 8 . Generally, these algorithms make some sacrifices to gain computational efficiency required to achieve appropriate statistical uncertainty levels.…”
Section: Introductionmentioning
confidence: 99%
“…( 8 , 9 ) This is due to assumptions inherent to the algorithm, such as the modeling of electron scatter with a Gaussian distribution and the lack of delta ray and Bremsstrahlung modeling. Some authors have already reported on the accuracy of macro Monte Carlo algorithms in the presence of heterogeneous media; ( 10 – 13 ) however, measurements were limited to regions located before or after the heterogeneity. Neuenschwander et al ( 3 ) performed validation simulations of MMC within bone and lung heterogeneity by comparing MMC results to EGS4 results.…”
Section: Introductionmentioning
confidence: 99%
“…1a and b) were arranged using small solid blocks of PMMA. The dimensions of these cavities were chosen as representative geometries of cavities presented in the head and neck region [7,14] and are summarized in Table 1. For all phantom configurations, a PMMA plate (15 Â 15 cm 2 area) with thickness of 0.2 cm was located at the top of the phantom block containing the cavities.…”
Section: Phantom Geometrymentioning
confidence: 99%
“…However, shallow cavities can affect the clinical result in several radiotherapy treatments [14,16]. Furthermore, Ding et al [13] reported that the accuracy of pencil beam calculations may depend not only on the geometry of the 3D inhomogeneity, but also on the location of the inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation